A Língua como mercado: uma análise do discurso sobre as relações entre a linguagem e o mercado no capitalismo contemporâneo - Graciano, Daniel Perico (Universidade Federal de São Carlos, 2024)
We assume that workers' languistic competence, in these times of symbolic activity hegemony, functions as an indispensable part of the sum of physical and intellectual abilities necessary for capitalist production. Thus, the power of community cohesion, based on communication, is also co-opted to compose power relations that converge on capitalist exploitation. To demonstrate this, we analyze a series of signs and symptoms that show and thematize the role of language in the production processes that derive surplus value from the capture of semiotic flows. To do so, the study is based on the theoretical-methodological postulates of Foucauldian discourse studies and Discourse Analysis as developed by Michel Pêcheux and his group. Our corpus is selected from a series of statements, according to the collection method known as the “snail method” (CHAREAUDEAU, 2011). That is, it is constructed from the search and identification of “signs-symptoms”, which, in one way or another, have presented themselves as representatives of the investigated problem. We will describe and interpret what they say and the ways in which they are formulated when they deal with the relationships between work and language that are established in the midst of a series of social transformations that contribute to the consolidation of linguistic work. We will thus offer relevant contributions to discourse studies. This research is divided into two complementary parts, the first of which deals with formal factory work, and the second focuses on informal and unpaid work performed in maintaining the relations that constitute platform capitalism.
Language as a market: an analysis of the discourse on the relationship between language and the market in contemporary capitalism
Keywords: Análise do discurso; Estudos discursivos; Trabalho; Competência linguística; Capitalismo de plataforma; Discourse analysis; Discursive studies; Labor; Linguistic competence; Platform capitalism; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::TEORIA E ANALISE LINGUISTICA